Support of Equal and Unequal Income Distribution: the Role of Perceived Threats - Prusova, I.S.; Gorokhova, A.S. (Socialʹnaâ Psihologiâ i Obŝestvo, 2025)
Objective. Analysis of the role of perceived threats in support of equal and unequal income distribution.Background. Global crises affect people's socio-economic well-being by causing various fears. Internal threats, subjective perception of threats and societal threats lead to the support of attitudes that legitimize inequality in the economic sphere. Previous research did not examine post-Soviet countries where egalitarianism, along with meritocracy, could also represent a defense ideology. This induces the question about the role of perceived threats in support of different principles of income distribution in the Russian context. Study design. The current study tested a model in which internal, societal threats, subjective perception of threats were included as predictors, support for equal and unequal distribution - as dependent variables, and socio-demographic characteristics - as control variables. Participants. 582 participants in Russia (49% of men, 51% of women) aged from 18 to 74 years (M = 37,38; SD = 11,27) took part in the study. Measurements. Study participants completed questionnaires on the fear of death (Wong et al.; Chistopol'skaya et al.), belief in a dangerous world and belief in a competitive world (Duckitt et al.; Gulevich et al.), support of equal or unequal income distribution (Kluegel & Smith; Prusova et al.), and financial threat scale to measure threats of socio-economic inequality and poverty (Marjanovic et al.; Prusova et al.).Results. The results of the structural equation modeling showed the adequate fit of this model: χ2 (378) = 847; RMSEA = 0,046 [0,042; 0,050]; SRMR = 0,051; TLI = 0,937; CFI = 0,944. Fear of death and belief in a competitive world positively contribute to support of unequal income distribution, while belief in a dangerous world and threat of socio-economic inequality enhanced support for equality in income distribution.Conclusions. The response to perceived threats is not universal and directly depends on the specifics of the threat. Internal threats actualize the desire for material profit, leading to support of unequal income distribution. Societal threats lead to support of equal income distribution as a guarantee of preserving social order under increased uncertainty. Цель. Анализ роли воспринимаемых угроз в поддержке политики равного и неравного распределения доходов. Контекст и актуальность. Глобальные кризисы влияют на социально-экономическое благополучие людей, вызывая различные страхи. Результаты многочисленных исследований показывают, что переживание личных, социетальных угроз, представление о мире как опасном или конкурентном приводят к поддержке установок, легитимизирующих неравенство в экономической сфере. Однако в таких работах не рассматривались страны постсоветского пространства, в которых, наряду с меритократическими ценностями, принцип эгалитаризма также может выполнять защитную функцию. В связи с этим возникает вопрос о роли воспринимаемых угроз в поддержке различных принципов распределения доходов в российском контексте. Дизайн исследования. В настоящем исследовании была построена модель, в рамках которой переживание личных угроз (страх смерти), социетальных угроз (социально-экономического неравенства и бедности), представление о мире как опасном или конкурентном (вера в опасный мир и вера в конкурентный мир) рассматривались в качестве предикторов поддержки политики равного и неравного распределения доходов, социально-демографические характеристики рассматривались в качестве контрольных переменных. Участники. В исследовании приняли участие 582 жителя России (49% мужчин, 51% женщин) в возрасте от 18 до 74 лет (M = 37,38; SD = 11,27). Методы (инструменты). Участникам исследования предлагалось заполнить русскоязычные версии методик: «Отношение к смерти» (П.Т.П. Вонг и др.; К.А. Чистопольская и др.), «Вера в опасный мир» и «Вера в конкурентный мир» (Дж. Даккит и др.; О.А. Гулевич и др.), «Шкала финансовой угрозы» для измерения переживания угрозы бедности и социально-экономического неравенства (З. Марьянович и др.; И.С. Прусова и др.) и «Поддержка равного/неравного распределения доходов» (Дж.Р. Клюгель и Е.Р. Смит; И.С. Прусова и др.). Результаты. Результаты моделирования структурными уравнениями показали, что протестированная модель находит полное соответствие данным: χ2 (378) = 847; RMSEA = 0,046 [0,042; 0,050]; SRMR = 0,051; TLI = 0,937; CFI = 0,944. Страх смерти и вера в конкурентный мир вносят положительный вклад в поддержку политики неравного распределения доходов, в то время как вера в опасный мир и переживание угрозы социально-экономического неравенства - в поддержку политики равного распределения доходов. Основные выводы. Ответ на воспринимаемые угрозы не является универсальным и напрямую зависит от специфики данных угроз. Переживание личных угроз актуализирует стремление к материальной выгоде, что находит выражение в поддержке политики неравного распределения доходов. Переживание социетальных угроз может приводить к поддержке политики равного распределения доходов как гарантии сохранения социального порядка в условиях повышенной неопределенности.